Kidnapped - Stevenson, Robert Louis, 1850-1894.; McFarlan, Donald, 1952- (London ; New York : Penguin Books, 1994)
After being kidnapped by his villainous uncle, sixteen-year-old David Balfour escapes and becomes involved in the struggle of the Scottish highlanders against English rule.
Keywords: Scotland -- History -- 18th century -- Juvenile fiction; Scotland -- History -- 18th century -- Fiction; Adventure and adventurers -- Fiction; English fiction -- Children's stories; Historical fiction